Effects of web-based versus classroom-based STEM learning environments on the development of collaborative problem-solving skills in junior high school students - Lin, Kuen-Yi; Yu, Kuang-Chao; Hsiao, Hsien-Sheng; Chang, Yu-Shan; Chien, Yu-Hung (International journal of technology and design education, 2020)
Collaborative problem-solving skills are one of the key competencies required in the twenty-first century. In this study, researchers attempted to compare the effectiveness of web-based collaborative problem-solving systems (wCPSS) and classroom-based collaborative hands-on learning activities (cCHLA) in the development of collaborative problem-solving skills in junior high school students who were learning science, technology, engineering, and mathematics (STEM)-related subjects. A quasi-experimental, nonequivalent pretest–posttest control group design was employed, and 241 junior high school students were invited to participate in the study. According to the results, a wCPSS-supported environment with teacher guidance was found to be more effective than either a wCPSS-supported environment without teacher guidance or a cCHLA-facilitated environment in developing students’ collaborative problem-solving skills in STEM fields. The study suggested that a web-based collaborative problem-solving system with teacher guidance can be used in developing junior high students’ collaborative problem-solving skills in STEM education.